Development of Biopesticide Bauveria bassiana Bals. (Vuill.) Fungi For Pest Control Vegetable in Berastagi - Sularno Sularno (Program Studi Pendidikan Biologi, 2018)
This research was conducted in two stages. The research method is the isolation and application of biopesticide. In the first stage aims to isolate entomopathogenic fungi Beauveria bassiana around Berastagi vegetable farms and grow on agar and corn mashed artificial medium. Testing the virulence of Beauveria bassiana in vitro in several types of vegetable pests before it is applied on agricultural land. In phase II aims to application B. bassiana in the vegetable patch. In the in vitro treatment, the ability to infect insects beauvria average reached 75%. , Controls on crop lands, in the third week began their Crocidolomia pests that attack the growing point so that the cabbage plants fail to bloom. Average cropland applied biopesticides B. bassiana has been no attack. At week 7 attacks on control plants reach 13 plants or 17.3%. In field applied while Beauveria bassiana attack reached six plants, or about 8%.